The Application of Polybutyl Cyanoacrylate (PBCA) Nanoparticles in Delivering Cancer Drugs - Salehi, Vahid; Izadkhah, Mohaddeseh; Salehi, Hanifeh; Sadeghi Pour, Niki; Ghanbarikondori, Parizad (Asian Pacific Journal of Cancer Biology, 2024)
Background: Cancer remains a significant global health challenge, accounting for one in eight deaths worldwide. Chemotherapy, the primary cancer treatment, is often limited by drug resistance. Optimizing therapy procedures has been suggested to improve survival and quality of life for cancer patients, including those with drug resistance. In recent years, nanotechnology has garnered significant attention for its potential in cancer treatment. Nanoparticles (NPs) are widely utilized to enhance therapeutic outcomes by improving drug bioavailability, solubility, and retention time. NPs offer essential conditions for targeted drug delivery through various delivery systems, including microcapsules or NPs. Polybutyl cyanoacrylate (PBCA) is among the most commonly used carriers for drug delivery in cancer treatment, with several studies investigating its efficacy. Methods: This article aims to review the effectiveness of PBCA as a drug delivery system in the treatment of various cancers. Results: Several studies have utilized PBCA for drug delivery in cancer treatment, indicating its potential efficacy in this regard. Conclusion: The review highlights the potential of PBCA as a promising drug delivery system for the treatment of different types of cancer.